PTSD in the armed forces: What have we learned from the recent cohort studies of Iraq/Afghanistan?. (2013) - Goodwin, Laura; Rona, Roberto J.
Abstract : Post-traumatic stress disorder (PTSD) was formally recognised as a psychiatric disorder in 1980, largely in response to America's attempts to make sense of the costs of the Vietnam war [Wessely, S., & Jones, E. (2004). Psychiatry and the 'lessons of Vietnam': What were they, and are they still relevant? War & Society, 22 (1), 89–103.]. Interestingly, all of this occurred without much contribution from epidemiology, which came later (Wessely & Jones, 2004). This cannot be said of the current conflicts, where from the outset there has been a focus of attention on the epidemiology of PTSD in those who served in either Iraq or Afghanistan, even whilst the conflicts were ongoing. In this editorial, we focus on this recent epidemiological contribution to the understanding of PTSD in military personnel.